(untitled) (Research, Society and Development, 2023)
Carambola (Averrhoa carambola) is a fruit that belongs to the Oxalidaceae family, being widely consumed in Asia and Central and South America, besides, its leaves are also used for their medicinal properties. However, carambola contains oxalic acid and caramboxin in its composition, which can cause nephrotoxicity, being a risk for those who ingest the fruit. This study aims to describe and discuss the effects of star fruit consumption in previously healthy patients and the occurrence of acute kidney injury. This is a narrative review, in which the databases of Scielo, PubMed and Google Scholar were used to support the present study, including 7 articles which demonstrate that, although the fruit has proteins, lipids, carbohydrates, fibers, water, vitamins and nutrients in its composition, it can cause nephrotoxicity due to oxalic acid, leading to acute kidney injury. Furthermore, it was verified that the sour carambola contains more oxalate than the sweet fruit, and the lethal dose ranges from 2 to 30g. Therefore, even though it appears to be a harmless fruit, it can lead to the development of acute nephropathy due to excessive ingestion of oxalic acid and caramboxin contained in it, requiring investigation in patients who present with acute kidney injury, with no apparent etiology.